“THE ROLE OF MULTIMEDIA TOOLS IN DEVELOPING STUDENTS’ MUSICAL LITERACY IN CONTEMPORARY EDUCATION” - Ochilov Zayniddin Saypiddinovich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
ABSTRACT: This article examines the use of multimedia tools in music education and their impact on developing students’ musical literacy. The study highlights how audio, visual, and interactive digital resources can enhance students’ understanding of musical theory, performance skills, and creative abilities. Emphasis is placed on the pedagogical benefits of integrating technology into music lessons to increase engagement, motivation, and independent learning.